Pengaruh Kualitas Sumber Daya Manuisa, Profesionalisme Kerja Dan Komitmen Tergadapa Kinerja Pegawai (Studi Pada Kantor Kecamatan Bancar Kabupaten Tuban) - Rizka Fitriyatul Ilmiyah; Abdul Kodir Djaelani; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the influence of human resource quality, work professionalism and commitment to employee performance at the Bancar District office, Tuban Regency. The type of research used in this study is quantitative research. The method used is multiple linear regression. The sampling technique uses saturated samples with a total sample of 33 employees. The results showed that simultaneously the variables of human resource quality, work professionalism, and commitment had a significant effect on employee performance. And there is a partial influence between the influence of human resource quality, work professionalism, and commitment to employee performance.  Keywords: Quality Of Human Resources, Work Professionalism, Commitment, Employee Performance.